Degradable NaCeF4-based up / down conversion luminescent material and preparation method and application thereof

By doping Yb3+, Tm3+ and Zr4+ ions with NaCeF4 matrix, degradable NaCeF4:Yb, Tm, Zr materials were prepared, which solved the problem that traditional NaYbF4 matrix materials were difficult to degrade in biological bodies, and simplified the preparation process and achieved efficient fluorescence imaging effects.

CN119662256AActive Publication Date: 2025-03-21SHANDONG NORMAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411830269.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The traditionally converted luminescent materials of the existing NaYbF4 matrix are difficult to degrade in biological bodies, resulting in long-term accumulation of materials in tissues, causing poisoning problems. At the same time, the preparation process of existing composite luminescent materials is complex and costly.

Method used

NaCeF4 is used as a matrix and doped with Yb3+, Tm3+ and Zr4+ ions, and a degradable NaCeF4:Yb, Tm, Zr material is prepared by hydrothermal reaction method. This material can simultaneously exhibit up-conversion and down-conversion multicolor fluorescence under specific wavelength excitation and has controllable degradability.

Benefits of technology

The controlled degradability of the material is achieved, the preparation process is simplified, the cost is reduced, and the good fluorescence imaging effect is shown in the biological body, with a potential contrast agent for fluorescence imaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662256A_ABST
    Figure CN119662256A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable NaCeF4-based up / down conversion luminescent material and a preparation method and application thereof, and belongs to the technical field of luminescent materials. The chemical formula of the degradable NaCeF4-based up / down conversion luminescent material is NaCeF4: Yb, Tm and Zr, and the molar ratio of Ce < 4 + > to Yb < 3 + > to Tm < 3 + > to Zr < 4 + > is (60-80): (18-22): (0.08-0.12): (2-20). The NaCeF4-based up / down conversion luminescent material provided by the invention has good degradability; the material is high in up-conversion emission efficiency, up-conversion emission Stokes displacement is improved to an ultraviolet region, up-conversion luminescence and down-conversion luminescence can appear at the same time under 980 nm laser irradiation, the material is expected to be used as a contrast agent for fluorescence imaging, the preparation process is simple and environmentally friendly, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of luminescent materials, and in particular to a degradable NaCeF 4 Up / down conversion luminescent material and preparation method and application thereof. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Rare earth doped upconversion luminescent materials have the characteristics of low toxicity, no background fluorescence, and high light penetration depth. They are good fluorescent contrast agents and have good application prospects in disease diagnosis, biological detection and imaging. Fluoride has low phonon energy (<400cm -1 ), high refractive index, strong chemical stability, high optical transparency, narrow emission band, etc., it is a widely used upconversion luminescent matrix material. 4 Due to its high fluorescence quantum yield and excellent fluorescence performance, it has become a widely studied object by researchers. 4 The matrix has a stable lattice structure and is difficult to degrade in the body. It accumulates in the tissue for a long time, causing acute or chronic poisoning. To address this problem, some researchers prepared Na 3 ZF 7 / K 3 ZF 7 Upconversion nanoparticles based on K 3 ZF 7 This arrangement of the lattice makes Yb 3+ / Er 3+ A series of red rare earth-doped inorganic upconversion nanocrystals (UCNCs) can be prepared by doping into a high-symmetry matrix. The nanoparticles contain water-soluble [ZrF 7 ] 3- Clusters can show good degradability under low pH conditions, and rare earth ion doping can achieve upconversion luminescence under near-infrared light excitation. 3 ZF 7 / K 3 ZF 7 The formation of the matrix requires doping with a large amount of zirconium ions, a large amount of [ZrF 7 ] 3-The formation of clusters often leads to rapid degradation of materials, which is uncontrollable. Moreover, the synthesis process requires a completely water-free and oxygen-free environment, which is extremely harsh and has poor repeatability. In addition, due to the different nano-wavelength lasers of different luminescent materials, composite luminescent materials in the prior art often require the preparation of lasers with different nano-wavelengths, which is expensive and has high experimental costs. Therefore, it is urgent to provide an up / down conversion nanomaterial with controllable degradation, simple preparation method and the ability to simultaneously achieve multi-color luminescence. Summary of the invention

[0004] In view of this, the present invention provides a degradable NaCeF 4 Based on up / down conversion luminescent material and preparation method and application thereof, the NaCeF provided by the present invention 4 The degradation process of the up / down conversion luminescent material is controllable, and the preparation process does not require the removal of water and oxygen. Moreover, it can simultaneously exhibit up-conversion and down-conversion multi-color fluorescence under the excitation of a specific wavelength exciter, and the up-conversion luminescence has a long Stokes shift that can reach the ultraviolet region.

[0005] In a first aspect, the present invention provides a degradable NaCeF 4 Based on up / down conversion luminescent material, its chemical formula is NaCeF 4 :Yb,Tm,Zr, among which Ce 4+ , Yb 3+ 、Tm 3+ and Zr 4+ The molar ratio is (60-80):(18-22):(0.08-0.12):(2-20).

[0006] In a second aspect, the present invention provides the above-mentioned degradable NaCeF 4 A method for preparing an up / down conversion luminescent material comprises the following steps:

[0007] Mixing and dissolving a cerium source, an ytterbium source, a thulium source and a zirconium source in water according to a stoichiometric ratio to obtain a mixed salt solution;

[0008] Add fluoride aqueous solution and sodium hydroxide aqueous solution to the mixed salt solution, stir evenly and then carry out hydrothermal reaction, wash and dry the obtained solid product to obtain the product.

[0009] In a third aspect, the present invention provides the above-mentioned degradable NaCeF 4 Application of up / down conversion luminescent materials, wherein the degradable NaCeF 4 The up / down conversion luminescent materials are used to prepare contrast agents for fluorescence imaging.

[0010] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0011] (1) NaCeF provided by the present invention 4 The up / down conversion luminescent material has good degradability, and the degradation time of the material can be conveniently controlled by adjusting the doping ratio of zirconium ions; the material has good dispersibility in aqueous solution and PBS solution, high up conversion emission efficiency, the Stokes shift of up conversion emission is increased to the ultraviolet region, and up conversion luminescence and down conversion luminescence can appear simultaneously under 980nm laser irradiation. By utilizing the higher tissue penetration depth of its down conversion luminescence, it is expected to realize fluorescence imaging in vivo, and can be used as a contrast agent for fluorescence imaging;

[0012] (2) The preparation method provided by the present invention is very simple and does not require a harsh anhydrous and oxygen-free environment. The synthesis of the material can be completed using water as a solvent, which is environmentally friendly and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0014] Figure 1 It is NaCeF of Example 1 of the present invention 4 : X-ray diffraction patterns of Yb, Tm, Zr materials;

[0015] Figure 2 It is NaCeF of Example 1 of the present invention 4 : Transmission electron microscope images of Yb, Tm, Zr materials;

[0016] Figure 3 It is NaCeF of Example 1 of the present invention 4 : Up-conversion emission spectra of Yb, Tm, Zr materials under the excitation of 980nm laser;

[0017] Figure 4 It is NaCeF of Example 1 of the present invention 4 : Down-conversion emission spectra of Yb, Tm, and Zr materials under the excitation of 980nm laser;

[0018] Figure 5 It is NaCeF of Example 1 of the present invention 4 : Transmission electron microscope images of Yb, Tm, and Zr materials after 48 hours of degradation;

[0019] Figure 6 It is NaCeF of Example 1 of the present invention 4 : Fluorescence spectra of Yb, Tm, and Zr materials at different degradation times;

[0020] Figure 7 It is NaCeF of Example 1 of the present invention 4 : Fluorescence intensity images of Yb, Tm, and Zr materials at different degradation times;

[0021] Figure 8 It is the fluorescence spectra of the materials of Examples 1 to 3 and Comparative Example 1 of the present invention after 48 hours of degradation;

[0022] Fig. 9 It is NaCeF of Example 1 of the present invention 4 : Down-conversion near-infrared second-zone fluorescence images of Yb, Tm, Zr materials in PBS solution;

[0023] Fig.10 The NaCeF 4 : Down-conversion near-infrared zone II fluorescence image of Yb, Tm, and Zr in mice (A) and near-infrared zone II imaging of mouse vascular sections (B). DETAILED DESCRIPTION

[0024] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0025] The present invention provides a degradable NaCeF 4 Based on up / down conversion luminescent material, its chemical formula is NaCeF 4 :Yb,Tm,Zr, among which Ce 4+ , Yb 3+ 、Tm 3+ and Zr 4+ The molar ratio is (60-80):(18-22):(0.08-0.12):(2-20).

[0026] The NaCeF provided by the present invention 4 Based on up / down conversion luminescent materials, NaCeF 4 As the matrix, Yb 3+ 、Tm 3+ and Zr 4+ As doping ions, Yb 3+ As a sensitizing ion, Tm 3+ As the luminescence center, Zr 4+ The upconversion nanocrystals are endowed with a soft lattice structure so that they can be degraded under physiological conditions. 4+ , Yb 3+ 、Tm 3+ and Zr4+ The total molar amount of Na + The molar ratio is 1:1.

[0027] The NaCeF provided by the present invention 4 The up / down conversion luminescent material has good degradability, and the degradation time of the material can be conveniently controlled by adjusting the doping ratio of zirconium ions; the material has good dispersibility in aqueous solution and PBS solution, high up-conversion emission efficiency, the up-conversion emission Stokes shift is increased to the ultraviolet region, and up-conversion luminescence and down-conversion luminescence can appear simultaneously under 980nm laser irradiation.

[0028] In the present invention, Ce 4+ , Yb 3+ 、Tm 3+ and Zr 4+ The molar ratio is more preferably (65-75):(19-21):(0.09-0.11):(8-20).

[0029] The present invention provides the above-mentioned degradable NaCeF 4 A method for preparing an up / down conversion luminescent material comprises the following steps:

[0030] Mixing and dissolving a cerium source, an ytterbium source, a thulium source and a zirconium source in water according to a stoichiometric ratio to obtain a mixed salt solution;

[0031] Add fluoride aqueous solution and sodium hydroxide aqueous solution to the mixed salt solution, stir evenly and then carry out hydrothermal reaction, wash and dry the obtained solid product to obtain the product.

[0032] In the present invention, the cerium source is selected from one or more of cerium chloride, cerium nitrate or cerium acetate; the ytterbium source is selected from one or more of ytterbium chloride, ytterbium acetate, ytterbium sulfate or ytterbium nitrate; the thulium source is selected from one or both of thulium nitrate or thulium chloride; the zirconium source is selected from one or more of zirconium oxychloride, zirconium chloride, zirconium nitrate or zirconium acetate; the fluoride is selected from ammonium fluoride or sodium fluoride. In one or more embodiments of the present invention, the cerium source is selected from cerium chloride heptahydrate, the ytterbium source is selected from ytterbium chloride hexahydrate, the thulium source is selected from thulium chloride hexahydrate, the zirconium source is selected from zirconium nitrate pentahydrate, and the fluoride is selected from ammonium fluoride.

[0033] In the mixed salt solution of the present invention, the concentration of the cerium source is 0.05-0.2 mol / L. The concentration of the fluoride aqueous solution is 0.5-3 mol / L, and the concentration of the sodium hydroxide aqueous solution is 0.1-1 mol / L. The concentrations of the remaining substances can be calculated according to the set stoichiometric ratio. The appropriate concentration facilitates the hydrothermal reaction.

[0034] In the step of performing a hydrothermal reaction after stirring uniformly according to the present invention, the stirring time is 10 to 60 minutes, more preferably 20 to 40 minutes. During the stirring process, the cerium source, ytterbium source, thulium source and zirconium source react with sodium hydroxide to generate corresponding hydroxide precipitates, and the stirring process can promote the formation of precipitates.

[0035] In the present invention, the temperature of the hydrothermal reaction is 100-200°C, more preferably 140-160°C; the time of the hydrothermal reaction is 4-15h, more preferably 5-10h. The present invention does not impose any special restrictions on the heating rate of the reaction temperature of the hydrothermal reaction, and the present invention is preferably 3-8°C / min, more preferably 4-6°C / min. The present invention does not impose any special restrictions on the cooling rate after the hydrothermal reaction is completed, and it can be cooled naturally to room temperature or cooled to room temperature by water cooling, air cooling, etc.

[0036] The present invention does not impose any special restrictions on the process of obtaining the solid product after the hydrothermal reaction is completed, and the solid-liquid separation method commonly used in the art can be used, such as filtration, suction filtration or centrifugation.

[0037] The washing step of the present invention is specifically to wash with water and ethanol in sequence, and the washing times are 2 to 5 times. The washing process is to remove the raw materials that have not reacted completely and purify the obtained product.

[0038] The present invention does not impose any particular limitation on the drying process. The present invention preferably performs vacuum drying at 50-70° C. until the solvent is completely evaporated.

[0039] The preparation method provided by the present invention is very simple, does not require a harsh anhydrous and oxygen-free environment, and can complete the synthesis of the material using water as a solvent. It is environmentally friendly and low-cost.

[0040] The present invention also provides the above-mentioned degradable NaCeF 4 Application of up / down conversion luminescent materials, wherein the degradable NaCeF 4 The up / down conversion luminescent materials are used to prepare contrast agents for fluorescence imaging.

[0041] The technical solution of the present invention is further described below in conjunction with specific examples. The present invention has no particular limitation on the sources of the reagents used in the following examples, and commercially available products known to those skilled in the art can be used.

[0042] Example 1

[0043] This embodiment provides a degradable NaCeF 4 Up / down conversion luminescent materials (NaCeF 4 :Yb, Tm, Zr) preparation method.

[0044] S1, weigh 0.699mmol CeCl 3 7H 2 O, 0.200mmol YbCl 3 6H 2 O, 0.001mmolTmCl 3 6H 2 O, 0.100mmolZr(NO 3 ) 4 ·5H 2 O, 4mmol NH 4 F and 1mmol sodium hydroxide were used as reaction raw materials;

[0045] S2, the CeCl weighed in step S1 3 7H 2 O was added to a beaker, dissolved in 5 mL of deionized water, and then YbCl 3 6H 2 O, TmCl 3 6H 2 O, Zr(NO 3 ) 4 ·5H 2 O Mix and stir at room temperature for 10 min to obtain a mixed salt solution;

[0046] S3, add 1mmol / mL NH 4 4 mL of F aqueous solution and 4 mL of 0.25 mmol / mL NaOH aqueous solution were added to generate a white precipitate, which was stirred for 30 min to obtain a precursor dispersion;

[0047] S4, adding the precursor dispersion obtained in step S3 into a hydrothermal kettle, then placing the hydrothermal kettle in an oven, heating it to 150°C at a heating rate of 5°C / min, reacting for 8h, and then cooling it to room temperature to obtain a product;

[0048] S5, centrifuging the product in step S6, washing it with deionized water and anhydrous ethanol three times in sequence, and drying it in a vacuum oven at 60°C to obtain NaCeF 4 :Yb, Tm, Zr powder materials.

[0049] Figure 1 The NaCeF 4 : X-ray diffraction patterns of Yb, Tm, and Zr materials. X-ray diffraction (XRD) analysis shows that it is consistent with the JCPDS75-1924 standard card data, showing 2θ peaks at approximately 16.6° (100), 23.5° (001), and 28.9° (110). Figure 2 The NaCeF4 : Transmission electron microscope images of Yb, Tm, and Zr materials show that NaCeF 4 The crystals are arranged in a uniform tetragonal phase.

[0050] Figure 3 The NaCeF 4 : Up-conversion emission spectra of Yb, Tm, Zr materials under the excitation of 980nm laser, Figure 4 is the down-conversion emission spectrum under the excitation of 980nm laser. It can be seen that NaCeF 4 :Yb, Tm, and Zr can simultaneously convert 980nm near-infrared light into multi-wavelength visible light (up-conversion emission) and near-infrared light in the second region (down-conversion emission).

[0051] Example 2

[0052] This embodiment provides a degradable NaCeF 4 Up / down conversion luminescent materials (NaCeF 4 :Yb, Tm, Zr) preparation method.

[0053] S1, weigh 0.699mmol CeCl 3 7H 2 O, 0.200mmol YbCl 3 6H 2 O, 0.001mmolTmCl 3 6H 2 O, 0.020mmolZr(NO 3 ) 4 ·5H 2 O, 4mmol NH 4 F and 1mmol sodium hydroxide were used as reaction raw materials;

[0054] S2, the CeCl weighed in step S1 3 7H 2 O was added to a beaker, dissolved in 5 mL of deionized water, and then YbCl 3 6H 2 O, TmCl 3 6H 2 O, Zr(NO 3 ) 4 ·5H 2 O Mix and stir at room temperature for 10 min to obtain a mixed salt solution;

[0055] S3, add 1mmol / mL NH 44 mL of F aqueous solution and 4 mL of 0.25 mmol / mL NaOH aqueous solution were added to generate a white precipitate, which was stirred for 30 min to obtain a precursor dispersion;

[0056] S4, adding the precursor dispersion obtained in step S3 into a hydrothermal kettle, then placing the hydrothermal kettle in an oven, heating it to 150°C at a heating rate of 5°C / min, reacting for 8h, and then cooling it to room temperature to obtain a product;

[0057] S5, centrifuging the product in step S6, washing it with deionized water and anhydrous ethanol three times in sequence, and drying it in a vacuum oven at 60°C to obtain NaCeF 4 :Yb,Tm,Zr powder.

[0058] Example 3

[0059] This embodiment provides a degradable NaCeF 4 Up / down conversion luminescent materials (NaCeF 4 :Yb, Tm, Zr) preparation method.

[0060] S1, weigh 0.699mmol CeCl 3 7H 2 O, 0.200mmol YbCl 3 6H 2 O, 0.001mmolTmCl 3 6H 2 O, 0.200mmolZr(NO 3 ) 4 ·5H 2 O, 4mmol NH 4 F and 1mmol sodium hydroxide were used as reaction raw materials;

[0061] S2, the CeCl weighed in step S1 3 7H 2 O was added to a beaker, dissolved in 5 mL of deionized water, and then YbCl 3 6H 2 O, TmCl 3 6H 2 O, Zr(NO 3 ) 4 ·5H 2 O Mix and stir at room temperature for 10 min to obtain a mixed salt solution;

[0062] S3, add 1mmol / mL NH 44 mL of F aqueous solution and 4 mL of 0.25 mmol / mL NaOH aqueous solution were added to generate a white precipitate, which was stirred for 30 min to obtain a precursor dispersion;

[0063] S4, adding the precursor dispersion obtained in step S3 into a hydrothermal kettle, then placing the hydrothermal kettle in an oven, heating it to 150°C at a heating rate of 5°C / min, reacting for 8h, and then cooling it to room temperature to obtain a product;

[0064] S5, centrifuging the product in step S6, washing it with deionized water and anhydrous ethanol three times in sequence, and drying it in a vacuum oven at 60°C to obtain NaCeF 4 :Yb,Tm,Zr powder.

[0065] Comparative Example

[0066] The difference between this comparative example and Example 1 is that Zr(NO 3 ) 4 ·5H 2 O.

[0067] Test example

[0068] 1. NaCeF of Example 1 4 :Degradation experiment of Yb, Tm, Zr materials:

[0069] Accurately weigh 5 mg NaCeF 4 :Yb, Tm, Zr were dissolved in 10 mL PBS solution, and after uniform dissolution, they were placed in a 37 °C vacuum oven, and the fluorescence intensity values ​​of the solution were measured at 0 h, 1 h, 3 h, 6 h, 12 h, 18 h, 24 h and 48 h. Figure 5 After 48h degradation, NaCeF 4 : From the transmission electron microscopy images of Yb, Tm, and Zr materials, it can be seen that the nanoparticles gradually degraded into debris after 48 hours. Figure 6 It is NaCeF 4 :The fluorescence spectra of Yb, Tm, and Zr materials at different degradation times show that the signal intensity of each peak in the upconversion spectrum gradually decreases with the extension of degradation time. Figure 7 It is NaCeF 4 : From the fluorescence intensity pictures of Yb, Tm, and Zr materials at different degradation times, it can be seen that the fluorescence intensity gradually decreases with the extension of time.

[0070] Figure 8It is the fluorescence spectra of the materials of Examples 1 to 3 and Comparative Example 1 after 48 hours of degradation. It is found that the fluorescence intensity of the material of Comparative Example 1 (Zr doping amount is 0) is not significantly weakened, indicating that the material has not been degraded. The materials of Examples 1 and 3 are both significantly degraded, and the fluorescence intensity of the material of Example 2 is weakened. It can be seen that the degradation time can be controlled by adjusting the Zr doping amount.

[0071] 2. Fluorescence imaging experiment:

[0072] To demonstrate the tissue penetration and imaging ability of UCNPs in mice, NaCeF 4 : The PBS solution of Yb, Tm, and Zr was injected into the tail vein of mice to observe the fluorescence characteristics of the material in the mice. Fig. 9 NaCeF 4 : The down-conversion near-infrared second-zone fluorescence images of Yb, Tm, and Zr in PBS solution show that they have good dispersibility in PBS solution; near-infrared second-zone fluorescence imaging was performed on living bodies, such as Fig.10 As shown, it can be seen that NaCeF 4 :Yb, Tm, and Zr emit bright fluorescent signals in mice, proving the degradable NaCeF 4 Up / down conversion luminescent materials can be used to prepare contrast agents for fluorescence imaging.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A degradable NaCeF4-based up / down conversion luminescent material, characterized in that: Its chemical formula is NaCeF4:Yb,Tm,Zr, among which Ce 4+ , Yb 3+ 、Tm 3+ and Zr 4+ The molar ratio is (60-80):(18-22):(0.08-0.12):(2-20).

2. The degradable NaCeF4-based up / down conversion luminescent material according to claim 1, characterized in that: Ce 4+ , Yb 3+ 、Tm 3+ and Zr 4+ The molar ratio is (65-75):(19-21):(0.09-0.11):(8-20).

3. The method for preparing the degradable NaCeF4-based up / down conversion luminescent material according to any one of claims 1 to 2, characterized in that: The steps include: Mixing and dissolving a cerium source, an ytterbium source, a thulium source and a zirconium source in water according to a stoichiometric ratio to obtain a mixed salt solution; Add fluoride aqueous solution and sodium hydroxide aqueous solution to the mixed salt solution, stir evenly and then carry out hydrothermal reaction, wash and dry the obtained solid product to obtain the product.

4. The preparation method according to claim 3, characterized in that: The cerium source is selected from one or more of cerium chloride, cerium nitrate or cerium acetate; the ytterbium source is selected from one or more of ytterbium chloride, ytterbium acetate, ytterbium sulfate or ytterbium nitrate; the thulium source is selected from one or both of thulium nitrate and thulium chloride; the zirconium source is selected from one or more of zirconium oxychloride, zirconium chloride, zirconium nitrate or zirconium acetate; the fluoride is selected from ammonium fluoride or sodium fluoride.

5. The preparation method according to claim 3, characterized in that: In the mixed salt solution, the concentration of the cerium source is 0.05-0.2 mol / L; the concentration of the fluoride aqueous solution is 0.5-3 mol / L; and the concentration of the sodium hydroxide aqueous solution is 0.1-1 mol / L.

6. The preparation method according to claim 3, characterized in that: In the step of performing hydrothermal reaction after stirring evenly, the stirring time is 10 to 60 minutes.

7. The preparation method according to claim 3, characterized in that: The temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 4-15 hours.

8. The preparation method according to claim 7, characterized in that: The temperature of the hydrothermal reaction is 140-160° C., and the time of the hydrothermal reaction is 5-10 hours.

9. The preparation method according to claim 3, characterized in that: The washing comprises washing with water and ethanol in sequence, and the washing times are 2 to 5 times.

10. Use of the degradable NaCeF4-based up / down conversion luminescent material according to any one of claims 1 to 2 or the degradable NaCeF4-based up / down conversion luminescent material prepared by the preparation method according to any one of claims 3 to 9, characterized in that: The degradable NaCeF4-based up / down conversion luminescent material is used to prepare a contrast agent for fluorescence imaging.

Citation Information

Patent Citations

  • Biodegradable up-conversion core-shell nanocrystal and preparation method and application thereof

    CN112940711A

  • Degradable up-conversion inorganic nano-material in living body, preparation method and application thereof

    CN113072939A

  • Degradable white and near-infrared two-region dual-mode light-emitting nanocrystal as well as preparation method and application thereof

    CN117186889A